(untitled) (Movimento-revista de educação, 2016)
Levando em conta diversas questões que emergem da discussão sobre a violência com jovens na sociedade contemporânea, este artigo, fruto dos debates promovidos pelo Grupo de Trabalho e Estudos sobre Políticas de Restrição e Privação de Liberdade da Universidade Federal Fluminense, tem como proposta analisar os dados divulgados no Brasil, através dos Mapas da Violência, nos últimos 15 anos. Para tanto, procura-se dialogar tanto com as pesquisas sobre os jovens como sujeitos da violência, quanto como vulneráveis à violência, propondo uma reflexão sobre as questões que hoje perpassam o debate sobre a redução da maioridade penal no país. Palavras-chave: violência, juventude, maioridade penal. Taking into account a number of issues that emerge from the discussion on violence with young people in contemporary society, this article, presents the result of debates promoted by the Working Group and Studies Restriction Policies and Deprivation of Liberty, Universidade Federal Fluminense. The aim of the article is to analyze the data disclosed in Brazil, using the Violence Maps in the last 15 years as research sources. The article intends to produce a dialogue with research results in which young people are subjects of violence as well as the vulnerable ones. A reflection on the issues that currently permeate the debate on the reduction of legal age in the country is addressed at the end of the article. Keywords: violence, youth, criminal responsibility.